IMPLEMENTASI PROMOTION MIX DALAM MENINGKATKAN JUMLAH PENGUNJUNG PADA GRAND ROYAL BIL HOTEL DI DESA BATUJAI KECAMATAN PRAYA BARAT - LOMBOK TENGAH - Dewi Rispawati (Journal of Innovation Research and Knowledge, 2024)
This research is entitled “Implementation of Promotion Mix in Increasing the Number of Visitors at Grand Royal BIL Hotel in Batujai Village, Praya District - Central Lombok”. This study aims to increase the Promotion Mix that will be used in increasing the number of visitors to the Grand Royal BIL Hotel in Batujai Village, West Praya District - Central Lombok. The method used in this research is descriptive with a qualitative approach. This study uses a triangulation technique analysis through data validity checks. In this study using the type of data, namely qualitative data and quantitative data and in research using data sources, namely primary data and secondary data. Based on the results of research entitled “Implementation of Promotion Mix in Increasing the Number of Visitors to the Grand Royal BIL Hotel in Batujai Village, West Praya District - Central Lombok”, the Promotion Mix that can be implemented to increase the number of visitors to the Grand Royal BIL Hotel in Batujai Village, West Praya District - Central Lombok includes: personal selling, sales promotion, mass selling, public relations and direct marketing. By implementing Promotion Mix in increasing the number of visitors to the Grand Royal BIL Hotel in Batujai Village, West Praya District - Central Lombok, so that the Grand Royal BIL Hotel is better known to the public on Lombok Island in particular to foreign countries which can increase the number of visitors to the Grand Royal BIL Hotel